Preserving Simalungun Culture through AI-Enhanced Curriculum Development: The SIMALOKA Approach - Hadiani Fitri (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Research on the preservation of local culture amidst globalization emphasizes the importance of a systematic educational strategy aligned with government policy. The main focus of this study is the role of educational institutions in introducing and maintaining the sustainability of Simalungun culture, considering that the cultural knowledge of the younger generation is declining due to modernization and the influence of the media. The research objective was to develop and evaluate SIMALOKA, an artificial intelligence-based framework with a teacher-in-the-loop approach that integrates Simalungun language, arts, rituals, and crafts into both formal and non-formal curricula. The method used combines natural language processing to tag content, a knowledge graph to map cultural concepts and skills, and a multi-objective optimization algorithm to develop balanced learning modules according to the cultural calendar. The system was tested using a dataset containing 1,850 cultural learning objects and produced modules with an average cultural coverage deviation of 3.4%, a content relevance score of 0.92, and an engagement rate of 87.1%, superior to two state-of-the-art baseline models. The results show that the combination of AI-based optimization and human validation can maintain cultural authenticity while significantly increasing student participation. These findings strengthen the hypothesis that context-sensitive, technology-based curriculum design can strengthen local cultural identity without neglecting educational policy demands. The study's conclusions confirm that SIMALOKA is a large-scale model that can be adapted to other local cultures, providing important implications for policymakers, educators, and cultural organizations in maintaining the sustainability of cultural heritage. Future research directions are directed at assessing long-term retention, resource constraints, and cross-cultural adaptation to make cultural preservation more inclusive and effective.